Building Bridges Triple P: Pilot study of a behavioural family intervention for adolescents with autism spectrum disorder. (May 2018) - Mazzucchelli, Trevor G.; Jenkins, Marian; Sofronoff, Kate
Abstract: Background: Many parents of adolescents with autism spectrum disorder (ASD) report that they are ill-equipped to support their children's behaviour, and these youths are known to be at substantially greater risk of emotional or behavioural problems compared to their typically developing peers. There is a need for an efficient and tailored parenting program for parents of adolescents with ASD that includes guidance on how to best support these youths' development and well-being. Aims: The current study examined the feasibility of Building Bridges Triple P (BBTP), an eight-week (11.5 h) parenting program specifically targeted to the needs of parents of adolescents with a developmental disability. Methods: A pretest-posttest single group design was used to evaluate the feasibility and acceptability of BBTP, and the potential of the program to have desired intervention effects, with nine parents of adolescents with ASD. Results: After participating in BBTP, parents reported significant reductions in their adolescent's behaviour problems, increased parenting confidence, decreased lax and overreactive responding, and decreased symptoms of depression and stress. These effects were mostly observed at post-test but were more pronounced at 3-month follow-up. Parents reported that they were satisfied with the content and format of BBTP. Conclusions: Results provide preliminary support for the feasibility and acceptability of BBTP, and that the program has a number of desired intervention effects.